PELAYANAN LINTAS BUDAYA: SEBUAH KAJIAN TENTANG PELAYANAN RASUL PAULUS DALAM KISAH PARA RASUL 16:13-40 - Harming; Gilbert Yasuo Imanuel; Yogi Darmanto (Vox Dei: Jurnal Teologi dan Pastoral, 2020)
Strategy in a mission is very important to learn, especially if you are missioning in a different cultural context. Strategy is the method used to achieve the goal. Meanwhile, cross-cultural service is an activity or effort in providing services to others in different cultural contexts and adjusting to the existing culture. In his ministry, Paul applied special cross-cultural services to the people of the city of Philippi in Acts 16: 13-40. In this article, the author uses the literature study method to conduct a study of cross-cultural services carried out by Paul. Based on a study of the text of Acts 16: 13-40, the writer found that there were four mission strategies of Paul in the city of Philippi in the context of cross-cultural service, namely winning souls in the area of ​​origin, not compromising with sin, performing miracles and winning the respected people.